KAJIAN DAN SOLUSI TEORI DAN PERILAKU ORGANISASI ATAS KORUPSI - Rizky Dermawan Soemanagara, (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
What creates corruption? How to solve the matter? This article attempts to uncover the radix of and offers solutions to reduce corruption from the perspective of organization theory and organization behaviour. Several key points are addressed such organizational structure and organizational culture. The agency theory and “an extended” social contract theory are used as main ideas to describe the historical, organizational key factors to the creation of corruption